Pengaruh Penggunaan Metode Buzz Grup terhadap Peningkatan Hasil Belajar Siswa Kelas IV Mata Pelajaran Matematika - Nida Mauizdati; Rofiatun Nisa'; Isti Nurkholipah (PUSAT PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT (P3M) SEKOLAH TINGGI ILMU TARBIYAH AL-FATTAH SIMAN LAMONGAN, 2021)
This study aims to determine the effect of using the buzz group method on improving the learning outcomes of fourth grade students in mathematics. This buzz group method aims to train students in discussing, exchanging opinions with their friends, growing self-confidence, and making learning active and fun, so that it can affect student learning outcomes. This research method uses an experimental method consisting of an experimental class and a control class. The experimental class received the buzz group method and the control class did not receive the buzz group method in learning. The instrument in this study was to use a test in the form of questions. From the data collection that has been obtained, the calculation results obtained the average value of the experimental class is 60, while the control class has an average value of 45.67. Based on the results of observations that have been made, it shows that the buzz group method has good criteria for use in the learning process activities, this is evidenced by the persentage value of the observer I 90%, observer II 77,5%, Besides that it also proven based on the result of research by testing the hypothesis using the t test on the data analysis that has been carried out the results t_count = 2.624 t_table = 2.05 with a significance level of 5%, and observer III 77,5%. then H_1 is accepted, meaning that there is a difference between the scores of students' mathematics learning outcomes in the experimental class and the control class. It means that one of the factors that affect the improvement of student learning outcomes is the teacher’s skills in managing the class, one of which is by using interesting learning methods such as the buzz group method